Use of Titanium Spiral Tacks for Long-term Oophoropexy Before Pelvic Irradiation. Issue 6 (1st July 2014) - Perri, Tamar; Ben-Baruch, Gilad; Davidson, Tima; Beiner, Mario E.; Helpman, Limor; Hogen, Liat; Jakobson-Setton, Ariella; Meirow, Dror; Haim, Simona Ben; Korach, Jacob
Abstract : Background: Ovarian transposition before planned pelvic irradiation can preserve ovarian function in young patients with pelvic malignancies. The transposed ovaries are fixed to the posterolateral abdominal wall. We described the use of a titanium spiral tack as a fixation device and compared it with other methods of oophoropexy. Methods: Medical and surgical records of all consecutive patients who underwent oophoropexy in our institution between 2007 and 2013 were reviewed. Demographic and clinical data were summarized; follicle-stimulating hormone values, recorded; and imaging scans, reviewed. Results: Oophoropexy was performed in 30 patients: 28 with cervical carcinomas and 2 with pelvic sarcomas. The procedure was done through laparoscopy in 13 patients and through laparotomy in 17. Titanium spiral tack was used for ovarian fixation in 14 patients, Vicryl suturing in 14, and in 2 cases the ovaries were pulled up through a retroperitoneal tunnel and fixed to the peritoneum with sutures. Titanium spiral tack fixation took a few seconds to perform. There were no immediate intraoperative or postoperative complications. Ovarian function was preserved in 15 patients (7/14 with spiral tack, 6/14 with sutures, and in both patients with retroperitoneal tunneling). Postoperative imaging results showed that all ovaries retained their extrapelvic location for a median period of 11.6 months (range, 2.3–63 months). Conclusions: Spiral tack is a simple, reliable method for oophoropexy before pelvic irradiation. Its efficacy is comparable with that of suture fixation, with the added advantage of ultrashort operative time. It is therefore worth considering as an alternative to suturing.